Studying the Effect of MgO Addition on the Thermal and Electrical Properties for Iraqi Porcelain - Mahdi, Duraid Fawzi (Al-Nahrain Journal of Science, 2017)
The research was studied effect of addition Magnesium Monoxide (MgO) on the thermal and electrical properties of Iraqi Porcelain with different weight percentages were (0%, 5%, 10%, 17%, 23% and 30%). The Porcelain was hard type and consist of (50%wt) Kaolin, (25%wt) Potassium Feldspar and (25%wt) Flint and sieving process was achieved for all powders and the particle sizes were (<125µm with 50%wt), (<75µm with 35%wt) and (<250µm with 15%wt) for Kaolin. The other particle sizes were (<75µm) for Potassium Feldspar, (<75µm) for Flint and (<63µm) for MgO. The powders were formed into disc shapes with diameters (10mm) and (40mm) by semi-dry pressing with (3 ton) applied pressure and Glycine (organic material) was added to powders through forming process with one drop to one gram from powder as a binder. The specimens were sintered in electrical furnace of (1250OC) for (2 hrs) as soaking time with increasing rate 7OC for one minute. The Bulk Density, Apparent Porosity, Specific Heat Capacity, Thermal Conductivity, Thermo- Compressive Strength and Dielectric Strength were studied. The best results for Specific Heat Capacity and Thermal Conductivity are F mixture with (30%MgO), Thermo- Compressive Strength is E mixture (23%MgO) and Dielectric Strength is C mixture (10%MgO).